Labor incorporation of professional Venezuelan immigrants in northern Chile - Berríos-Riquelme, José (2021)
This article describes the experiences of labor incorporation of a group of professional Venezuelan immigrants in northern Chile. The stories of the participants show that their experiences have been stressful for not being able to certify their degrees, having to take on jobs for those who are over-qualified, and in which they suffer exploitation and discrimination. It is concluded that the participants have had a break in their life cycle that they classify as stressful, and that the discrimination suffered is supported by the "Chilean migration policy". Finally, future lines of research are suggested, and policy implications are discussed.